China's pure exporter subsidies - Fabrice Defever; Alejandro Ria\~no (Center for Economic Studies and ifo Institute (CESifo), 2012)
One third of Chinese exporters sell more than ninety percent of their production abroad. We argue that this distinctive pattern is attributable to a wide range of subsidies that provide incentives to these pure exporters. We propose a heterogeneous-firm model in which firms exporting all their output receive an ad-valorem sales subsidy. Using microdata on manufacturing firms matched with custom transactions for the years 2000-2006, we measure sizable differences in productivity and paid taxes between pure exporters and domestic firms and between pure and regular exporters, in line with the predictions of our model. Embedding a pure-exporter subsidy in a two-country general equilibrium environment, we show that this instrument is worse from a welfare standpoint than a standard export subsidy, partly because it increases protection of the domestic market. A counterfactual analysis suggests that eliminating these subsidies would result in a welfare gain for China comparable to halving its trade costs.
Keywords: F12; F13; O47; 330; trade policy; export subsidies; heterogeneous firms; China; Exportsubvention; Exportindustrie; Wohlfahrtsanalyse; Schätzung; China